THE ASSOCIATION OF LOW TRIIODOTHYRONINE SYNDROME, PROTEIN-ENERGY WASTING AND CHRONIC INFLAMMATION WITH MORTALITY IN PREVALENT DIALYSIS PATIENTS - Črne Fureš, Nataša (Acta Clin Croat, 2018)
SUMMARY – This prospective study in prevalent dialysis patients investigated prognostic properties of low triiodothyronine syndrome, protein-energy wasting and chronic inflammation. Ninety-four prevalent dialysis patients were followed-up for a median of 39 months. Demographic, anthropometric and biochemical parameters were collected at baseline. Univariate and multivariate analysis was done using Cox regression analysis. ROC curve analysis using survival status as a classification variable was performed with the goal of determining optimal cut-off values for numerical variables. In our population, low total triiodothyronine (hazard ratio (HR) 2.19, p=0.038), catheter as vascular access (HR 2.76, p=0.023), higher vintage (HR 1.01, p=0.014) and higher Charlson comorbidity index (HR 1.28, p=0.017) were statistically significantly associated with inferior survival. In our group of steady-state dialysis patients, total triiodothyronine seemed to be the strongest predictor of inferior survival among thyroid hormones. Taking this parameter into account, it was possible to identify patients at an increased risk of death even after adjustment for other prognostically relevant variables. However, after further adjustment for significant risk factors, the impact of C-reactive protein and albumin on survival disappeared due to the overlapping prognostic properties. We concluded that triiodothyronine was an independent prognostic factor in our study group.